Potensi Wisata Dan Pengembangannya Di Nagari Limau Gadang Lumpo Kecamatan Iv Jurai Kabupaten Pesisir Selatan - Marganof, Marganof; Istiqamah, Lidya Putri; Yumarni, Yumarni (LPPM Universitas Muhammadiyah Sumatera Barat, 2026)
Nagari Limau Gadang Lumpo, Pesisir Selatan Regency, has natural tourism potential such as Batu Biduak River, Sarasah Talang Waterfall, rafting, and camping grounds. This potential supports the development of community-based ecotourism in the buffer zone of Kerinci Seblat National Park. However, tourism management remains limited due to inadequate infrastructure, lack of promotion, and low community capacity in management. This study aims to identify tourism potential and formulate appropriate development strategies in Nagari Limau Gadang Lumpo, IV Jurai District, Pesisir Selatan Regency. The area possesses various natural tourism assets, such as Sarasah Talang Waterfall, Batu Biduak River, and a camping ground, which have not yet been optimally managed. This research employs a qualitative descriptive method through observation, interviews, and literature review. The analysis refers to the ADO-ODTWA guidelines and uses SWOT analysis. The results indicate that most assessment aspects fall into the